a ! b ! = a ! + b ! + c 2
Let all the triplets of positive integer solutions of ( a , b , c ) satisfying the equation above be ( a 1 , b 1 , c 1 ) , ( a 2 , b 2 , c 2 ) , … , ( a n , b n , c n ) . Find ( a 1 + b 1 + c 1 ) + ( a 2 + b 2 + c 2 ) + ⋯ + ( a n + b n + c n ) .
Notation : ! denotes the factorial notation. For example, 8 ! = 1 × 2 × 3 × ⋯ × 8 .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
a ! b ! = a ! + b ! + c 2
a ! b ! − a ! − b ! = c 2
First consider a , b ≥ 5
Both a ! , b ! will end with zero.
So, a ! b ! has p + q number of zeroes where a ! and b ! has respectively p and q zeroes.
So, after subtraction the unequal number of zeroes i.e. p + q and other side p and q zeroes..But in perfect square there should be even number of zeroes at least.
So, there is no solution for greater than 5
Now consider 1 ≤ a , b ≤ 4
In this interval one can easily find the two ordered pair which satisfy the above equation.
Thy are 3 , 2 , 2 and 2 , 3 , 2
So, the answer is 1 4
Proof for a , b ≥ 5 is not correct. e.g. if a , b = 1 0 , 1 0 ! 2 − 2 ⋅ 1 0 ! = 1 0 ! ( 1 0 ! − 2 ) ends with an even number of zeroes.
We shall consider the case a,b greater than equals 5.then the given equation may be written as (a!-1)(b!-1)=c^2 +1 so for our case lhs is 1 modulo 10 so c=10k.so c^2+1 is 100k^2+1.but this is a prime no for all positive integer k.but the lhs is a product of 2 nos.since our case is a,both greater than or equals 5 neither of the factor of lhs is 1.o the case does not yield solutions.now we can take a=5 and b less than a.checking out the possible case b={2,3,4} obviously not 1 do not yield any solution.a=b also yeilds a=b=2 and c=0.(not positive).observe that if a,b is a solution then is b,a. So we have only 3 cases to check out a=4,b=3 and a=4,b=2 and a=3 ,b=2.
(a!-1)(b!-1)=(c^2)+1 Both sides must be 1 mod c. This can happen when the product's terms are either both -1 or both +1 mod c. If a;b>=c, then the modular equations are satisfied, because both a! and b! are divisible by c, but the magnitude is clearly off when c>3 (c<(c-1)!). +1 mod c doesn't work; if a;b<c then they're either -k mod c (k>1), or c units below c, that is, 0. So, the only solutions have to have 1=<c=<3
Problem Loading...
Note Loading...
Set Loading...
Rearrange the equation to get ( a ! − 1 ) ( b ! − 1 ) = c 2 + 1 ( 1 ) First note that c 2 + 1 doesn't have any prime divisor of the form p = 4 k + 3 . Let's prove it. Assume that c 2 + 1 has a prime divisor with p ≡ 4 3 . Then c 2 ≡ p − 1 and by Fermat's little theorem c p − 1 ≡ p 1 . On the other hand c p − 1 ≡ p ( c 2 ) 2 p − 1 ≡ p ( − 1 ) 2 k + 1 ≡ p − 1 This is a contradiction and completes the proof.
Now observe that if one of a or b is greater than 3 , LHS of equation ( 1 ) has at least one prime divisor in the form 4 k + 3 . For example if a ≥ 4 then a ! − 1 ≡ 4 3 and a ! − 1 does have a prime divisor of the form 4 k + 3 , otherwise all of its prime divisors will be of the form 4 k + 1 and a ! − 1 will be congruent to 1 ( m o d 4 ) . So we must have a ≤ 3 and b ≤ 3 . Trying few remaining cases for a and b we get 2 solutions: ( a , b , c ) = ( 2 , 3 , 2 ) , ( 3 , 2 , 2 )